2011
DOI: 10.1007/s10577-011-9186-7
|View full text |Cite
|
Sign up to set email alerts
|

The centrosome and spindle as a ribonucleoprotein complex

Abstract: 1 The Subject in ContextThe presence of nucleic acids in centrosomes and the spindle have been proposed, observed, and reported since the 1950s. Why did the subject remain, perhaps even until today, such a controversial issue? The explanation is manifold, and includes legitimate concern over contamination from other cellular compartments in biochemical preparations. With a typically high background of cytoplasmic ribosomes, even microscopic images of stained intact cells could be difficult to interpret. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Additionally we find this phenomenon in very conserved DNA genome content such as telomeres and centromeres (Witzany, 2008;Alliegro, 2011).…”
Section: The Agents Of Natural Genetic Engineering and Natural Genomesupporting
confidence: 51%
“…Additionally we find this phenomenon in very conserved DNA genome content such as telomeres and centromeres (Witzany, 2008;Alliegro, 2011).…”
Section: The Agents Of Natural Genetic Engineering and Natural Genomesupporting
confidence: 51%
“…The centrosome is the major microtubule organizing center of most animal cells and directs the formation of the mitotic spindle in dividing cells . While the centrosome is often discussed as a proteinaceous organelle, there are longstanding hints that RNA may contribute to its biology (see Marshall and Rosenbaum and Alliegro). There are multiple, non‐exclusive hypotheses for the function of RNA at centrosomes (Figure ).…”
Section: The Contribution Of Rna Localization To Acute Cellular Respomentioning
confidence: 99%
“…A single-stranded RNA ring (memorized linearly in DNA, which encodes nine different molecular labels, in an orderly sequence and equally spaced) possesses all the characteristics to be the molecular platform of the non-equivalence of the nine centriolar blades. A ring of RNA can, in turn, bind different polypeptides to form ribonucleoproteins [22] or various oligosaccharides [23].…”
Section: Hypothesis: An Rna Ring Generates the Circumferential Polarimentioning
confidence: 99%
“…Hiedemann et al, reported RNase sensitivity of Chlamydomonas basal bodies; Snyder [24] showed that RNase inhibited microtubule nucleation in PtK1 cells; Alliegro et al, [22,[25][26][27] isolated centrosomal RNAs (cnRNAs), absent from the remaining cytoplasm, in Spisula Solidissima; Chichinadze [28] and colleagues continued the studies on Spisula cnRNAs, focusing attention on a reverse transcriptase domain and a ribonucleoprotein consensus RNA-binding site contained in one of cnRNAs. The importance of RNA in centrosomes has been reaffirmed also by Ishigaki et al showing that RBM8A/MAGOH heterodimer (a member of exon junction complex on exporting mRNA, required for mRNA splicing, mRNA export and nonsense-mediated mRNA decay) formed a complex in centrosomes.…”
Section: Centrosomal Rnamentioning
confidence: 99%